2021
DOI: 10.3389/fphys.2021.687046
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation Attenuates Mechanical Allodynia and Increases Central Resolvin D1 Levels in Rats With Spared Nerve Injury

Abstract: Mounting evidence from animal models of inflammatory and neuropathic pain suggests that inflammation regulates the resolution of pain by producing specialized pro-resolving mediators (SPMs), such as resolvin D1 (RvD1). However, it remains unclear how SPMs are induced in the central nervous system and whether these mechanisms can be reconciled with outcomes of neuromodulation therapies for pain, such as spinal cord stimulation. Here, we show that in a male rat model of neuropathic pain produced by spared nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Intrathecal injection of adipose tissue-derived stem cells in rats selectively reduces cold, but not mechanical, allodynia following L5 spinal nerve ligation ( Jwa et al, 2020 ). On the contrary, electrical stimulation of the spinal cord of SNI rats was found to reduce injury-induced mechanical allodynia without affecting cold allodynia ( Tao et al, 2021 ). Additional differences exist between rodent species.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal injection of adipose tissue-derived stem cells in rats selectively reduces cold, but not mechanical, allodynia following L5 spinal nerve ligation ( Jwa et al, 2020 ). On the contrary, electrical stimulation of the spinal cord of SNI rats was found to reduce injury-induced mechanical allodynia without affecting cold allodynia ( Tao et al, 2021 ). Additional differences exist between rodent species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the expression levels of NLRP3 and IL-1β are elevated in several rodent neuropathic pain models [ 50 , 101 ]. But one team reported that SNI could not alter the expression of spinal NLRP3 inflammasome components (including IL-1β) [ 102 ], contradicting the results reported by others that SNI increased the expression of IL-1β in the serum, cerebrospinal fluid [ 103 ], and spinal cord [ 104 , 105 ]. In the present work, the administration of rrTNF to cultured BV2 cells or primary ACC neurons elevated the protein levels of Piezo1 and NLRP3 ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“… 358 Animal models of inflammatory and neuropathic pain show inflammation regulates pain resolution by producing pro‐resolving mediators such as resolvin D1 (RvD1). 318 Resolvins are derived from, eicosapentaenonic, docosahexanoic, docosapentaenoic, and clupanodonic omega‐3 fatty acids 317 , 359 , 360 and have cell regulatory properties similar to prostaglandins promoting the restoration of normal cellular functional properties following resolution of inflammatory conditions that occur with tissue injury. Resolvins are induced in the CNS following trauma and offer exciting possibilities in the development of potential methods for the alleviation of intractable neuropathic pain in chronically affected patients.…”
Section: Mammalian Agents With Pain Alleviating Propertiesmentioning
confidence: 99%